2018
DOI: 10.1111/cfs.12626
|View full text |Cite
|
Sign up to set email alerts
|

Parental empowerment and child behavioural problems during youth care involvement

Abstract: The aim of this study was to examine changes in parental empowerment and child behavioural problems during a period of youth care and how changes are related to the kind of services provided. We compared a preservation service that was familycentred (FCS) with out-of-home services that were primarily child-centred (CCS).The sample consisted of 621 families who were supported by FCS (n = 434) or CCS (n = 137). Information about parental empowerment and child behavioural problems was gathered at the start and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Staff members may increase the frequency of contact with parents when they notice changes in family empowerment. This may also lead to them encouraging parents to strengthen their parenting competencies (for instance, by improving parental monitoring, reducing parenting stress, and improving parent-child relationship problems) -an important component of empowerment (Damen et al, 2019). In this case, one may have expected staff familycentered attitude and behavior to relate to family empowerment as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staff members may increase the frequency of contact with parents when they notice changes in family empowerment. This may also lead to them encouraging parents to strengthen their parenting competencies (for instance, by improving parental monitoring, reducing parenting stress, and improving parent-child relationship problems) -an important component of empowerment (Damen et al, 2019). In this case, one may have expected staff familycentered attitude and behavior to relate to family empowerment as well.…”
Section: Discussionmentioning
confidence: 99%
“…Family characteristics associated with severe behavioral problems include parent-child relationship problems (Carr, 2019), poor parental monitoring (Biglan et al, 2004;Harder et al, 2017), and high levels of parenting stress (Vermaes et al, 2014). Higher parental involvement and monitoring, as well as empowerment and resilience processes (Liebenberg, 2020) can mitigate the development of severe behavior problems in adolescents (Biglan et al, 2004;Damen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use the term family therapy if any member of the extended family or other important relationships was involved in the treatment. Home treatment is offered at home with a broad scope, ranging from parenting skills, family relationships, and practical as well as emotional support [ 24 ]. Storytelling is a method to treat preverbal trauma in young children.…”
Section: Methodsmentioning
confidence: 99%
“…Research has revealed that family-centered programs were associated with increased empowerment of parents and decreased behavioral problems of children (Damen et al 2019;De Graaf et al 2008;Dunst et al 2007;Graves and Shelton 2007;Thompson et al 1997;Whittingham et al 2009). For example, parents experienced more personal control over their family life and were more willing to make efforts to learn new ways to help their children to grow and develop when they were engaged during treatment, they were completely informed of their rights, and they had access to an individual support plan that was tailored to the family demands (Thompson et al 1997).…”
Section: Psychological Empowerment Of Parents Increases During Intens...mentioning
confidence: 99%
“…Moreover, child behavioral problems decreased when helpgiving practices were individualized and responsive to the priorities and concerns of families and when they were focused on the involvement of parents in realizing their own goals (Dunst et al 2007). In addition, Damen et al (2019) and Graves and Shelton (2007) studied how changes in the empowerment of parents and behavioral problems of children were related and whether these changes in empowerment and behavioral problems are determined by familycenteredness of programs. Their findings indicate that the relation between family-centeredness and decreased behavioral problems of children is mediated by increased parental empowerment.…”
Section: Psychological Empowerment Of Parents Increases During Intens...mentioning
confidence: 99%